Chemical Fuel Mediated Self‐Regulatory Polymer Brushes for Autonomous Fluorescence Modulator and Wettability Switcher. Issue 7 (4th February 2022) - Li, Mengyuan; Ma, Ziwen; Pan, Chunyu; Zhang, Xiaoye; Zhang, Wenke; Yang, Bai; Li, Yunfeng
Abstract: Synthetic systems of nonequilibrium self‐assembly have made considerable progress; however, the achievement of innovative materials with self‐regulated functions analogous to living systems remains a grand challenge. Herein, a versatile nonequilibrium system of polymer brushes with spatiotemporally programmable properties and functions driven by chemical fuels is reported. By combining a responsive polymer with an autonomous pH regulator, the polymer brushes self‐regulate their swelling and deswelling process with tunable lifetimes. By using patterned copolymer brushes with pH‐responsive fluorescence moiety, an autonomous fluorescence modulator is created that self‐regulates its fluorescence in spatiotemporally programmable fashion driven by a chemical or an enzymatic reaction. Furthermore, a self‐regulated wettability switcher of polymer brushes both in air and in an aqueous solution is implemented. The methodology and results in the work provide a useful avenue into the exploration of nonequilibrium synthetic materials with programmable functions and would accelerate the transformative developments of nonequilibrium materials and systems in practical applications. Abstract : By integrating chemical or enzymatic reaction networks with stimuli‐responsive polymers, a versatile nonequilibrium synthetic system of polymer brushes is presented that self‐regulates their morphology and properties and functions in a spatiotemporally programmable way. Under the action of chemical fuels, the polymer brushes can be used as an autonomous fluorescence modulator and a wettability switcher.